On the Dimension of the Pullback Attractors for g-Navier-Stokes Equations - Delin Wu (Discrete Dynamics in Nature and Society)
We consider the asymptotic behaviour of nonautonomous 2D g-Navier-Stokes equations in bounded domain Ω. Assuming that f∈Lloc2, which is translation bounded, the existence of the pullback attractor is proved in L2(Ω) and H1(Ω). It is proved that the fractal dimension of the pullback attractor is finite.